Association Between Joint Hypermobility and Gastroesophageal Reflux Disease: An Observational Analytical Cross Sectional Study - Ziad AL-R AWI,; Faiq GORIAL,; Ayman ALI SALMAN, (Archives of Rheumatology, 2016)
Objectives: This study aims to assess the association between joint hypermobility (JHM) and gastroesophageal reflux disease (GERD). Patients and methods: This cross sectional study included 100 consecutive Iraqi patients (43 males, 57 females; mean age 30±6.6 years; range 18 to 40 years) with GERD diagnosed by a gastroenterologist according to the guidelines for diagnosis and management of GERD and age and sex matched 100 healthy controls (36 males, 64 females; mean age 30±5.2 years; range 20 to 40 years). JHM was measured using Beighton score method by a blinded observer. A score of 4 or more was considered hypermobile. Results: Joint hypermobility values were significantly higher in GERD patients than in controls [46 (71.9%) vs 18 (28.1%), p<0.001, odds ratio=3.88; 95% confidence interval=2.04-7.39]. Multiple logistic regression analysis to detect predictors of GERD in JHM patients revealed that patients with high total mobility score (7-9) had the highest risk for developing GERD [about 41 fold compared to those with normal mobility score (<4), P model <0.001, and overall prediction accuracy of 68%]. Conclusion: There is a significant association between JHM and GERD. The high total mobility score (7-9) was associated with a significantly high risk for developing GERD, indicating that early recognition of JHM may assist in early diagnosis and treatment of GERD.